Implementation of Sustainable Food Agriculture Land Protection Policy in Supporting Food Security in Indramayu Regency, West Java Province - Habdul Manan; Mawar Mawar; Maya Puspita Dewi; Izzatusholekha Izzatusholekha (Journal of World Science, 2025)
This article discusses the implementation of the Sustainable Agricultural Land Protection Policy (PLP2B) in Indramayu Regency, West Java Province, which aims to support national food security. The study analyzes the challenges, strategies, and successes in maintaining agricultural land sustainability amidst the rapid conversion of land to non-agricultural uses. The findings indicate that, although significant regulatory efforts are in place, ongoing land conversion remains a major challenge. The Indramayu Regency Government continues to address this issue through policies involving various stakeholders, including the central government, local government, private sector, and communities. This research provides important insights into the effectiveness of these policies in achieving long-term food security goals.